2011
DOI: 10.1108/00242531111153597
|View full text |Cite
|
Sign up to set email alerts
|

Career choice, satisfaction, and perceptions about their professional image

Abstract: Purpose -The purpose of this paper is to investigate the factors affecting career choice, job satisfaction, and perceptions of the public image of librarians in Kuwait. Design/methodology/approach -Data were gathered via questionnaires sent to 117 professional librarians working in academic, public, and special libraries in Kuwait. Findings -The study identified factors which influenced the choice of career, sources of satisfaction and dissatisfaction. Respondents reported that they were moderately satisfied w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Studies exploring the relationship between information professionals' satisfaction and years of professional experience have shown contradictory results. It has been found that job satisfaction diminished as the number of years of working experience increased (Mirfakhrai, 1991;Togia et al, 2004), while other studies have shown a positive relationship between length of work experience and job satisfaction (Alansari, 2011;Baro, Fyneman, & Zoukemefa, 2013;Berry, 2007;Van Reenen, 1998).…”
Section: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…Studies exploring the relationship between information professionals' satisfaction and years of professional experience have shown contradictory results. It has been found that job satisfaction diminished as the number of years of working experience increased (Mirfakhrai, 1991;Togia et al, 2004), while other studies have shown a positive relationship between length of work experience and job satisfaction (Alansari, 2011;Baro, Fyneman, & Zoukemefa, 2013;Berry, 2007;Van Reenen, 1998).…”
Section: Literature Reviewmentioning
confidence: 93%
“…The majority of studies that have examined job satisfaction have focused on academic libraries (Bernstein, 2011;Horenstein, 1993;Leckie & Brett, 1996;Leysen & Boydston, 2009;Mirfakhrai, 1991;Sierpe, 1999), and only a few have examined it with respect to information professionals working in a range of other organizations such as public, school, and special libraries, and archives (Alansari, 2011;Pors & Johannsen, 2002;Williamson, Pemberton, & Lounsbury, 2005). Even though the latter studies examine how satisfied employees are in a variety of organizations, they do not consider the differences in job satisfaction among them.…”
Section: Problem Statementmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, they found that the educational and occupational background of MLIS students got more diversified as a result of a growing interest in librarianship among non-library professionals. Other similar studies confirmed that the love of books and reading, interest in library work, pleasant library working environment and employment opportunities were important factors for people to choose a career in the library profession (Alansari, 2011; Hallam and Partridge, 2005).…”
Section: Literature Reviewmentioning
confidence: 86%
“…Taylor et al … (2010) surveyed to know the motivations for choosing a library career of MLIS students, and results show that an overwhelming majority of current MLIS students (76%) indicated that job function was the primary motivator in their decision to pursue librarianship as a career. Alansari (2011) investigated the factors affecting career choice, job satisfaction, and perceptions of the public image of librarians of 117 professional librarians working in academic, public, and special libraries in Kuwait. Respondents reported that they were moderately satisfied with their current job.…”
Section: Introductionmentioning
confidence: 99%